1999
DOI: 10.1210/jcem.84.6.5824
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Androgens and Carotid Intimal-Medial Thickness in Women

Abstract: The influence of endogenous androgens on atherosclerotic disease in women is unknown. In this study involving 101 pre- and post-menopausal females, we evaluated the relationship between serum androgen levels and both carotid artery intimal-medial thickness (IMT) and major cardiovascular risk factors. In addition to evaluation of blood pressure, body mass index, and waist-to-hip ratio, serum dehydroepiandrosterone sulfate (DHEA-S), androstenedione (A), total testosterone (TTS), free testosterone (FTS), insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
4
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 28 publications
4
47
4
3
Order By: Relevance
“…This speculation could explain why their role arises only in lean women, when the effect of adiposity is blunted. Consistently, previous studies reported that serum androstenedione and testosterone were inversely associated with intima-media thickness in pre-and postmenopausal women (48,49). We could also speculate that the protective effect of androgens on inflammation might contain the increase in the risk of cardiovascular events that is expected in PCOS women, considering the many metabolic abnormalities they have.…”
Section: Discussionsupporting
confidence: 88%
“…This speculation could explain why their role arises only in lean women, when the effect of adiposity is blunted. Consistently, previous studies reported that serum androstenedione and testosterone were inversely associated with intima-media thickness in pre-and postmenopausal women (48,49). We could also speculate that the protective effect of androgens on inflammation might contain the increase in the risk of cardiovascular events that is expected in PCOS women, considering the many metabolic abnormalities they have.…”
Section: Discussionsupporting
confidence: 88%
“…The negative association of these atherogenic molecules with androgens advocates a probable role of androgens in cardiovascular protection in PCOS subjects. The role of androgens in cardiovascular risk factors in women with PCOS has been controversial; however, there are studies suggesting a protective role of androgens (28,29). Interestingly, no association of NGAL and MMP-9/NGAL complex with insulin resistance or hsCRP was demonstrated in this study, a finding that implies alternative pathways of NGAL and MMP-9 regulation.…”
Section: Discussioncontrasting
confidence: 68%
“…122 However, it is unclear whether this decline adversely affects vascular health in women. Higher serum testosterone concentrations, within the physiological range, have been associated with lower carotid intima-media thickness, 123 suggesting potential protective effects of endogenous testosterone on cardiovascular health in pre-and postmenopausal women. Conversely, it is well known that women with polycystic ovary syndrome, who exhibit high androgen levels, are at a higher risk for CVD.…”
Section: Testosterone Deficiency and Cvd In Womenmentioning
confidence: 99%